Harum manis / Rafidah Abas and Azila Azmi - Abas, Rafidah; Azmi, Azila (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
A group of researchers from the Faculty of Hotel and Tourism Management and Faculty of Chemical Engineering University Technology MARA Pulau Pinang branch successfully developed and launched 11 foods and homecare products from harumanis. The initiative, a joint effort between the university and the Department of Agriculture Perlis aims to diversify the harumanis market potential, whilst exploring areas for harumanis farmers to increase their income. The group of researchers are Dr Azila Azmi, Mr Mohamad Syazwan Osman and Mr Faizal Abdul Wahab.